2014
DOI: 10.1890/13-1977.1
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of warming on aphids, their predators, and ant mutualists

Abstract: Abstract. Species exist within communities of other interacting species, so an exogenous force that directly affects one species can indirectly affect all other members of the community. In the case of climate change, many species may be affected directly and subsequently initiate numerous indirect effects that propagate throughout the community. Therefore, the net effect of climate change on any one species is a function of the direct and indirect effects. We investigated the direct and indirect effects of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 32 publications
2
71
2
Order By: Relevance
“…However, the consequences of increased thermal variability can be system- and species-specific [43]. In some systems, the third trophic level benefits from increased temperatures, whereas the herbivore suffers from them [4345]. In others this response is reversed [46] or there is little or no change [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…However, the consequences of increased thermal variability can be system- and species-specific [43]. In some systems, the third trophic level benefits from increased temperatures, whereas the herbivore suffers from them [4345]. In others this response is reversed [46] or there is little or no change [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [25] suggested that a positive relationship might be expected based on the positive effect of temperature on pest growth rates [66]. However, the same logic applies to the mutualists and natural enemies of pests [67], making straightforward predictions difficult [68]. It is tempting to extend the relationship between insecticide use and GDD to say something about future insecticide use on a warming planet.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the well-documented sensitivity of top predators to landscape alteration (Purvis et al 2000;Martinson and Fagan 2014) but suggest that for grassland insect communities, the decline of top predators does not necessarily lead to predator-mediated effects on herbivore communities. However, recent studies have shown that the regulatory effect of top predators on insects can be context dependent as a function of seasonality (Gratton and Denno 2003), wind speed (Barton 2014), and especially temperature (Hoekman 2010;Shurin et al 2012;Barton and Ives 2014). In the current context of global change, caution is therefore required when predicting the relative importance of predatormediated processes versus plant-mediated processes, as it is likely to change as a function of the focal stressors.…”
Section: Discussionmentioning
confidence: 99%